Assessment of the visceral adipose tissue by magnetic resonance imaging in patients with coronary artery disease: link to metabolism disorders and condition of the abdominal aorta. (14th October 2021) - Ryumshina, N; Koshelskaya, O A; Kologrivova, I V; Kharitonova, O A; Ussov, W Y U
Abstract: Aim: MRI-quantification of the visceral and subcutaneous adipose tissue (AT) and investigation of its interconnections with anthropometric parameters of obesity, carbohydrate metabolism and condition of abdominal aorta in patients with chronic coronary artery disease (CAD). Methods: The study included 55 patients (mean age 61.2±7.2 y.o.) with chronic CAD. All patients underwent MRI of the abdominal AT and abdominal aorta segment on a 1.5 T MRI in standard modes. Calculation of the area and volume of abdominal subcutaneous (SAT) and visceral adipose tissue (VAT) was conducted at L4-L5 level; the total volumes of abdominal SAT and VAT were calculated. Parameters of lipid and carbohydrate metabolism as well adipokines' profile were measured in blood serum. Results: To eliminate gender bias the data in the total group was corrected for the sex, height and body weight. In the course of the multiple linear regression analysis, we detected the independent determinants, which described 95% of the total VAT volume variability and were represented by waist circumference and serum levels of HDL cholesterol and adiponectin. The model was characterized by the significance level p<0, ehab724.116501, the residues of the model were normal. The evaluation of the coefficients in the model was as following: 1, 39 for waist circumference, −0.26 for HDL cholesterol and −0, 19 for adiponectin. We detected direct correlation between the aorta diameter and total SAT volume (rs=0.30), which was independent from sex; and reverse correlations between the aorta diameter and HbA1c level (rs=−0.40) and postprandial glycemia (rs=−0.40). Patients with dilated aorta when compared to the patients with normal aorta diameter did not differ in the AT accumulation, but demonstrated decreased levels of HbA1c and postprandial glycaemia, which was dependent upon the lower numbers of patients with diabetes mellitus type 2. Conclusion: We have identified the independent determinants of the total volume of the abdominal visceral AT increase, which appeared to be increment of the waist circumference and decrease of the serum adiponectin and HDL cholesterol. Results of the study indicate the presence of the interconnection between the processes of the abdominal aorta remodeling, accumulation of subcutaneous adipose tissue and carbohydrate metabolism impairments. FUNDunding Acknowledgement: Type of funding sources: None.